Primary Head and Neck Tumour-Derived Fibroblasts Promote Lymphangiogenesis in a Lymphatic Organotypic Co-culture Model - Karina M. Lugo-Cintrón; José M. Ayuso; Mouhita Humayun; Max M. Gong; Sheena C. Kerr; Suzanne M. Ponik; Paul M. Harari; María Virumbrales-Muñoz; David J. Beebe (EBioMedicine, 2021)
Background: In head and neck cancer, intratumour lymphatic density and tumour lymphangiogenesis have been correlated with lymphatic metastasis, making lymphangiogenesis a promising therapeutic target. However, inter-patient tumour heterogeneity makes it challenging to predict tumour progression and lymph node metastasis. Understanding the lymphangiogenic-promoting factors leading to metastasis (e.g., tumour-derived fibroblasts or TDF), would help develop strategies to improve patient outcomes. Methods: A microfluidic in vitro model of a tubular lymphatic vessel was co-cultured with primary TDF from head and neck cancer patients to evaluate the effect of TDF on lymphangiogenesis. We assessed the length and number of lymphangiogenic sprouts and vessel permeability via microscopy and image analysis. Finally, we characterised lymphatic vessel conditioning by TDF via RT-qPCR. Findings: Lymphatic vessels were conditioned by the TDF in a patient-specific manner. Specifically, the presence of TDF induced sprouting, altered vessel permeability, and increased the expression of pro-lymphangiogenic genes. Gene expression and functional responses in the fibroblast-conditioned lymphatic vessels were consistent with the patient tumour stage and lymph node status. IGF-1, upregulated among patients, was targeted to validate our personalised medicine approach. Interestingly, IGF-1 blockade was not effective across different patients. Interpretation: The use of lymphatic organotypic models incorporating head and neck TDF provides insight into the pathways leading to lymphangiogenesis in each patient. This model provided a platform to test anti-angiogenic therapeutics and inform of their effectiveness for individual patients. Funding: NIH R33CA225281. Wisconsin Head and Neck SPORE NIH P50DE026787. NIH R01AI34749.